Peran Pendidikan Pancasila dan Kewarganegaran dalam Mengantisipasi Tindakan Cyberbullying di Lingkungan Sekolah (Studi Fenomenologi di SMA Pasundan 1 Bandung) - Salsabila Khairunnisa; Cahyono; Delila Kania (UNIVERSITAS SERAMBI MEKKAH, 2024)
As technology develops, it allows everyone, including children, to easily access social media and makes cyberbullying increasingly common. The aim of the research is to determine the role of Pancasila and Citizenship Education (PPKn) in overcoming cyberbullying in grade 11 and 12 students at Pasundan 1 Bandung High School, as well as the obstacles and ways to overcome them. The research was carried out using qualitative methods, with the theory or basis for the discussion coming from literature studies of journals, articles and books that are relevant to the research. The data analysis technique uses the Miles and Huberman interactive model with stages of data reduction, data presentation, drawing conclusions, and verification using interview data objects with the Principal, Deputy Principal, Civics Teacher, Counseling Teacher, 15 students (both perpetrators and victims of cyberbullying), and a psychologist. The research results show that the teaching staff has made efforts to become educators, mentors, advisors, supervisors, role models and motivators. Meanwhile, the challenges faced by PPKn teachers are the development of science and technology which is not supported by the ability to filter information, students' social interactions, parents who are less cooperative, the ability of PPKn teachers to supervise, and the teacher's ability to control students and social media. The proposed solution is to coordinate with all teachers, including guidance and counseling teachers, approach students and check cell phones.